1996
DOI: 10.1002/jhet.5570330108
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and theoretical calculations of novel 5‐aryl substituted 2,4,7‐trioxo and 4,7‐dioxo‐2‐thioxopyrido[2,3‐d]pyrimidines

Abstract: New substituted pyrido[2,3‐d]pyrimidines 5 and 6 have been prepared in one‐step from the readily available 6‐amino‐2,4‐dioxotetrahydropyrimidine (1) or 6‐amino‐4‐oxo‐2‐thioxotetrahydropyrimidine (2) and the arylidene substituted Meldrum's acid. The substitution pattern of the ethylene moiety in compounds 5 and 6 results in a strong push‐pull electronic effect. The semiempirical calculations using the AM1 method reveal two equally favoured conformations showing a distorted geometry. The calculated charge densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In the 1 H NMR spectra of products obtained, characteristic signals for the protons of the methyne fragment in the region δ 4.11-4.49 and nonequivalent protons of the methylene unit in the region δ 2.51-3.20 are observed, that is in good agreement with the literature data for analogous subjects. 1- 4 We have shown that, in contrast to approaches described earlier, 1-4 arylmethylidene derivatives of the Meldrum's acid are reasonable to be obtained directly in the reaction mixture, that decreases the number of steps for the process and virtually does not affect the yields of target products. In conclusion, the optimum method for the synthesis of thieno[2,3 b]pyridinones 4 is a three component condensation of aromatic aldehyde 8, the Meldrum's acid (2), and the corresponding salts 7 or acid 5 as the synthetic equivalents of labile 2 aminothiophene 3.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…In the 1 H NMR spectra of products obtained, characteristic signals for the protons of the methyne fragment in the region δ 4.11-4.49 and nonequivalent protons of the methylene unit in the region δ 2.51-3.20 are observed, that is in good agreement with the literature data for analogous subjects. 1- 4 We have shown that, in contrast to approaches described earlier, 1-4 arylmethylidene derivatives of the Meldrum's acid are reasonable to be obtained directly in the reaction mixture, that decreases the number of steps for the process and virtually does not affect the yields of target products. In conclusion, the optimum method for the synthesis of thieno[2,3 b]pyridinones 4 is a three component condensation of aromatic aldehyde 8, the Meldrum's acid (2), and the corresponding salts 7 or acid 5 as the synthetic equivalents of labile 2 aminothiophene 3.…”
mentioning
confidence: 80%
“…In the literature, there are data on the reaction of arylmethylidene derivatives of the Meldrum's acid 1 with stable heterocyclic analogs of enamines, viz., aminopyr azoles, 1,2 aminopyridazinones, 3 and aminopyrimidinones, 4 resulting in the annulation of the dihydropyridinone ring with the Meldrum's acid (2) which plays the role of C 2 synthon. However, the number of such stable amino heterocycles is limited.…”
mentioning
confidence: 99%
“…Dihydropyrazolo[3,4‐ b ]pyridinones were synthesized by heating of aminopyrazole ( 68 ) with different benzylidene derivatives of ethyl cyanoacetate ( 242 ) in the presence of triethylamine [112]. It was proven that the formation of the bicyclic product ( 244 ) occurred by oxidation of the intermediate ( 243 ; Scheme 60) [113–116].…”
Section: Other Methods Of Synthesis Of Pyrazolo[34‐b]pyridin‐6‐onesmentioning
confidence: 99%
“…11 In general, these dihydropyridones can be easily prepared from Meldrum's acid by a heterocyclization reaction of aˇ-keto ester or acetylacetone and an aromatic aldehyde in the presence of ammonium acetate. 12,13 In connection with our studies of novel calcium channel modulators, we have previously described the synthesis and conformational study of 5-alkoxycarbonyl-6-methyl-3,4-dihydropyridines 14 and 5-acetyl-4-aryl-3,4-dihydro-6-methyl-2(1H)-pyridones. 15 Recently we also reported a solid-phase synthesis method 16 and a solventfree synthesis under microwave irradiation of 5-alkoxycarbonyl-6-methyl-3,4-dihydropyridones.…”
Section: Introductionmentioning
confidence: 99%